MAS-1 adjuvant immunotherapy generates robust Th2 type and regulatory immune responses providing long-term protection from diabetes in late-stage pre-diabetic NOD mice. (August 2014) - Zhang, Li; Londono, Pilar; Yu, Liping; Grimes, Stephen; Blackburn, Peter; Gottlieb, Peter; Eisenbarth, George S.
Abstract MAS-1, a nanoparticular, emulsion-based adjuvant, was evaluated for its ability to promote Th2 and regulatory immune responses and prevent type 1 diabetes progression when given alone or as antigen-specific immunotherapy (ASI) using insulin B chain (IBC; MER3101) and its analog B:9-23(19Ala) (MER3102). MAS-1 formulations were administered to NOD mice at age 9 and 13 weeks and followed through 52 weeks. MER3101 and MER3102 provided long-term protection with 60% and 73% of mice remaining diabetes-free at week 35, and 60% and 47% at week 52. MAS-1 adjuvant emulsion by itself also provided protection with 60% and 40% of mice diabetes-free at 35 and 52 weeks, respectively. Higher levels of interleukin (IL)-10 and IL-2 positive T cells were detected among splenocytes by week 15 in MER3101 and MER3102 immunized mice, whereas MAS-1 alone induced higher levels of IL-10-positive T cells. Diabetes-free 52-week-old mice expressed significant levels of antigen-specific IL-10-positive type 1 regulatory T cells and FoxP3-positive T cells when stimulated ex vivo with IBC. Antibodies targeting IBC and B:9-23(19Ala) induced by MER3101 and MER3102 were overwhelmingly Th2 type IgG1 and IgG2b isotypes. Splenocyte cultures from 52 week diabetes-free, MER3101-treated mice secreted significantly increased levels of IL-4 and IL-5 Th2 cytokines. Based on these pre-clinical results and its clinical safety profile, MAS-1 has the requisite qualities to be considered for use in prophylactic or early stage disease settings to augment ASI to prevent disease progression in type 1 diabetes.